The development of professor's professional knowledge in Psychology - Cardós, Paula Daniela; Compagnucci, Elsa Rosa (2007)
This work belongs to the Project "Teaching and learning Psychology: a study of the educational practice in professors and beginners". It is part of an investigation program developed in the context of the subject "Didactic and Practical Planning of Psychology teaching" in which we have been working since 1998. This subject is also considered as the final stage of the formative itinerary for Psychology s professors. The reached results show the incidence that the beliefs and professors' representations have in the teaching processes. By getting into the studies centered in the educational knowledge we guide the inquiry around the development of the professor's professional knowledge and particularly the development of their formation. Our proposal contemplates a formation device which incorporates the observation, reflection, evaluation and self-evaluation of the practice in order to facilitate the reconstruction, significance and re-significance of the teaching and learning processes by giving relevance to the development of the teacher professional knowledge. The analysis of teaching practices process reveals that the mediations that cross the knowledge in the being taught instances are constituted in reflections axes. This involves the future professor's relationship with the knowledge and their projection in the construction of the professional identity.
Keywords: Teaching of Psychology; Formation device; Reflection; Professional knowledge